Integrated Target‐Based and Phenotypic Screening Approaches for the Identification of Anti‐Tubercular Agents That Bind to the Mycobacterial Adenylating Enzyme MbtA. (23rd September 2019) - Ferguson, Lindsay; Wells, Geoff; Bhakta, Sanjib; Johnson, James; Guzman, Junitta; Parish, Tanya; Prentice, Robin A.; Brucoli, Federico
Abstract: Iron is essential for the pathogenicity and virulence of Mycobacterium tuberculosis, which synthesises salicyl‐capped siderophores (mycobactins) to acquire this element from the host. MbtA is the adenylating enzyme that catalyses the initial reaction of mycobactin biosynthesis and is solely expressed by mycobacteria. A 3200‐member library comprised of lead‐like, structurally diverse compounds was screened against M. tuberculosis for whole‐cell inhibitory activity. A set of 846 compounds that inhibited the tubercle bacilli growth were then tested for their ability to bind to MbtA using a fluorescence‐based thermal shift assay and NMR‐based Water‐LOGSY and saturation transfer difference (STD) experiments. We identified an attractive hit molecule, 5‐hydroxyindol‐3‐ethylamino‐(2‐nitro‐4‐trifluoromethyl)benzene (5 ), that bound with high affinity to MbtA and produced a MIC90 value of 13 μm . The ligand was docked into the MbtA crystal structure and displayed an excellent fit within the MbtA active pocket, adopting a binding mode different from that of the established MbtA inhibitor Sal‐AMS. Abstract : An integrated target‐based and phenotypic screening method was developed and deployed to identify 5‐hydroxyindol‐3‐ethylamino‐(2‐nitro‐4‐trifluoromethyl)benzene (5 ) as an attractive hit molecule that was found to bind MbtA with high affinity, producing a MIC90 value of 13 μm .